EFFECT OF INTER-ORGANISATIONAL RELATIONSHIP ON COMMUNITY-BASED ORGANISATIONS' PERFORMANCE: EVIDENCE FROM OSUN STATE, NIGERIA - Kolawole A. ADELOYE; Banji O. ADISA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study examined effect of inter-organisational relationship on Community Based Organisations’ (CBOs) performance in rural areas. Data were gathered through structured interview schedule from 140 CBOs’ members and analysed using appropriate statistics. The results revealed that the mean age of CBOs’ members interviewed in the study area was 57.6 ± 15.1 years and had spent an average of 15.3 ± 9.5 years in formal school. Majority (72.1%) of the respondents was male and a lot (82.1%) of them joined CBOs because of their community development. The results also indicated that majority (84.3%) of the CBOs was registered with governmental agency; they had main focus on project execution (82.9%) with main (80.0%) source of fund from members’ contribution. There were significant association between improvement in CBOs’ performance and respondents’ main occupation (χ2= 40.45; ρ≤ 0.01); and reasons for joining CBOs (χ2= 29.04; ρ≤ 0.01), also there were positive and significant relationship between improvement in CBOs’ performance and members’ age (r=0.514; ρ≤ 0.01); and years of formal education (r=0.534; ρ≤ 0.01). As a result of the findings of the study, it was concluded that there was improvement in CBOs’ role performance due to inter-relationship among them. In order to maximize potentials inherent in inter-relationship among CBOs, it was recommended that all challenges, such as low level of government assistance, inadequate resources, differing culture and values of partnering CBOs, militating against it should be adequately addressed by the relevant stakeholders.